The Added Value of and Resistance to the Istanbul Convention: A Comparative Study in 27 European Member States and Turkey - Leye, Els; D’Souza, Hayley; Meurens, Nathalie (Frontiers in Human Dynamics, 2021)
The Council of Europe’s Istanbul Convention on VAW and Domestic Violence is a legally binding instrument tackling violence from a gender perspective. Although 21 European Union Member States and Turkey have ratified it and the European Union signed it, opposition towards gender equality has also risen. This paper reviews a study by the European Parliament, which aimed to understand the implementation of the Convention, its added value and arguments against its ratification. The EP Study grouped the 27 EU MS and Turkey into those that have and have not ratified and implemented the IC. Methodology: 1) literature review focusing on the impact of and arguments against ratification; 2) a legal mapping of the legislation to compare the criminal codes and support services of each country with relevant articles of the Convention; 3) national data collection to identify challenges in the implementation of the Convention and good practices; 4) a stakeholder on-line consultation. The EP study found that ratification of the Convention triggered amendments to existing legislation and/or the adoption of new legal measures, but that legislative changes are less extensive in countries that have not ratified the Convention. Most European Union MS have adopted gender-neutral approaches to laws and policies, thus failing to acknowledge the gendered nature of violence against women and domestic violence. Seven of the European Union countries refer to physical, psychological, economic and sexual violence in their definitions of domestic violence, while nine countries do not define domestic violence. Remaining challenges in the implementation of the Istanbul Convention include a lack of sustainable national action plans, and insufficient funding for specialist support services. Resistance to the Convention is evident even in countries that have ratified it, in response to proposed legislation on same-sex marriage, adoption or sexuality education in schools. Non-ratifying countries and countries with high resistance to the Convention often display victim-blaming public attitudes to intimate partner violence, stronger gender stereotypes and a stronger resistance to same-sex marriage/rights. The paper concludes by suggesting recommendations. Any legal and policy developments after September 16 2020 were not included, i.e. Poland and Turkey announcing their withdrawal from the IC.